ANALISIS PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Air Minum Dalam Kemasan Club di Semarang) - Widiaswara, Tias; Sutopo, Sutopo (Diponegoro Journal of Management, 2017)
This research is motivated by the decrease in customer satisfaction of Club mineral water that can influence the loyalty of Club mineral water customers. Based on the problem, this research aims to examine the effect of product quality and brand image on customer loyalty through customer satisfaction as the intervening variable.This research was conducted by distributing questionnaires to Club mineral water customers in Semarang with purposive sampling method. The samples used were 100 respondents of Club mineral water customers. The data were processed using software SPSS 23, and the analysis used were multiple linear regression analysis and test of Sobel to test the mediation effect of the independent variable to the dependent variable.The result showed that product quality and brand image have positive and significant effect to customer satisfaction with the result of Y1 = 0,331 X1 + 0,463 X2, and brand image, product quality, and customer satisfaction have positive and significant influence to customer loyalty with the result Y2 = 0,206 X1 + 0.318 X2 + 0.311Y1. The result of the Sobel test shows that there is influence between product quality to customer loyalty through customer satisfaction as the intervening variable. Similarly, the brand image variable has an influence on customer loyalty through customer satisfaction. This is because of the value of t arithmetic higher than t table.